Advances on P2P, Parallel, Grid, Cloud and Internet Computing : Proceedings of the 13th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2018) /: Proceedings of the 13th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2018). ([2019]) - Unknown
No abstract available